Focal Seizures and Posterior Reversible Encephalopathy Syndrome as Presenting Signs of IgA Vasculitis/Henoch-Schoenlein Purpura—An Educative Case and Systematic Review of the Literature - Funken, Dominik; Götz, Friedrich; Bültmann, Eva; Hennies, Imke; Gburek-Augustat, Janina; Hempel, Julya; Dressler, Frank; Baumann, Ulrich; Klemann, Christian (Frontiers in Neurology, 2021)
Background: Henoch-Schoenlein purpura (HSP) is a systemic small vessel vasculitis of unknown pathogenesis predominantly affecting children. While skin, GI tract, joints, and kidneys are frequently affected and considered, CNS involvement of this disease is underestimated. Methods: We provide a case report and review the literature on HSP systemically, collecting data on the spectrum of neurological manifestations. Results: We report on a 7-year-old girl with HSP who presented with diplopia and afebrile focal seizures, which preceded the onset of purpura. cMRI was consistent with PRES showing typical focal bilateral parieto-occipital swelling and cortical and subcortical high signal intensities on T2-FLAIR images, without signs of cerebral vasculitis as diffusion restriction was not found (apparent diffusion coefficient (ADC) negative). CSF analysis and blood tests excluded systemic inflammation or vasculitis. Interestingly, hypertension was not a hallmark of the developing disease in the initial phase of PRES manifestation. Renal disease and other secondary causes for PRES were also excluded. Supportive- and steroid treatment resulted in restitution ad integrum. Reviewing the literature, we identified 28 other cases of HSP with CNS involvement. Severe CNS involvement includes seizures, cerebral edema, or hemorrhage, as well as posterior reversible encephalopathy syndrome (PRES). 13 patients fulfilled all diagnostic criteria of PRES. The mean age was 11.2 years (median 8.0, range 5-42 years), with no reported bias towards gender or ethnic background. Treatment regimens varied from watchful waiting to oral and intravenously steroids up to plasmapheresis. Three cases showed permanent CNS impairment. Conclusion: Collectively, our data demonstrate that I) severe CNS involvement such as PRES is an underappreciated feature of HSP, II) CNS symptoms may precede other features of HSP, III) PRES can occur in HSP, and differentiation from CNS vasculitis is challenging, IV) pathogenesis of PRES in the context of HSP remains elusive, which hampers treatment decisions. We, therefore, conclude that clinical awareness and the collection of structured data are necessary to elucidate the pathophysiological connection of HSP and PRES.